Analysis of the Professional Competency of Islamic Religious Education Teachers in the Implementation of the Independent Curriculum - Munawir, Munawir; Lestari, Nurin Nihayah Fikma; Ahnaf, Aisha Faadihilah (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2025)
Purpose of the study: This study aims to describe and analyze the importance of professional competence of islamic religious education teachers, as well as the relevance of this professional competence to the demands of the Independent Curriculum. Methodology: This research is descriptive-based qualitative research with a literature study approach. Through analysis of documents such as scientific journals, books and related research reports. The data collection method in this study is information collection, using sources as the main data related to the professional competence of islamic religious education teachers, independent curriculum, and curriculum implementation. The data from the sources obtained is then analyzed in depth, evaluating the quality of the data sources, analyzing the data, interpreting the data, and drawing conclusions. Main Findings: (1) The professional competence of Islamic Religious Education teachers in teaching students has five criteria, namely: mastering the foundations of education, mastering teaching materials, compiling teaching programs, implementing learning programs, and assessing the results of the teaching and learning process that has been implemented. (2) The obstacle for islamic religious education teachers in teaching students is that islamic religious education teachers still do not understand the independent curriculum in terms of its application during learning. (3) There needs to be an increase in the competence of islamic religious education teachers in implementing the independent curriculum effectively for students in the learning process. Novelty/Originality of this study: The novelty of this research lies in the challenges and opportunities of professional competence of islamic religious education teachers and their application in the independent curriculum. This finding can produce a new model that can be used to develop the competence of islamic religious education teachers in the independent curriculum so that it can provide quite relevant information for islamic religious education teachers in Indonesia.